Transcriptomic Responses to Different Cry1Ac Selection Stresses in Helicoverpa armigera - Wei, Jizhen; Yang, Shuo; Chen, Lin; Liu, Xiaoguang; Du, Mengfang; An, Shiheng; Liang, Gemei (Frontiers in Physiology, 2018)
Helicoverpa armigera can develop resistance to Bacillus thuringiensis (Bt), which threaten the long-term success of Bt crops. In present study, RNAseq was employed to investigate the midgut genes response to strains with different levels of resistance (LF5, LF10, LF20, LF30, LF60 and LF120) in H. armigera. Results revealed that series of differentially expressed unigenes (DEGs) were sigificantly expressed in resistant strains compared with LF susceptible strain. Nine trypsin genes, ALP2 were significantly down-regulated in all the six resistant strains and were further verified by qRT-PCR, indicating that these genes may be used as markers to monitor and manage pest resistance in transgenic crops. Most importantly, the differences in DEG functions in the different resistant strains revealed that different resistance mechanisms may develop during the evolution of resistance. The immune and detoxification processes appear to be associated with the low-level resistance (LF5 strain). Metabolic process-related macromolecules possibly lead to resistance to Cry1Ac in the LF10 and LF20 strains. The DEGs involved in the ‘proton-transporting V-type ATPase complex’ and the ‘proton-transporting two-sector ATPase complex’ were significantly expressed in the LF30 strain, probably causing resistance to Cry1Ac in the LF30 strain. The DEGs involved in binding and iron ion homeostasis appear to lead to high level resistance in the LF60 and LF120 strains, respectively. The multiple genes and different pathways seem to be involved in Cry1Ac resistance depending on the levels of resistance. Although the mechanisms of resistance are very complex in H. armigera, a main pathway seemingly exist, which contributes to resistance in each level of resistant strain. Altogether, the findings in the current study provide a transcriptome-based foundation for identifying the functional genes involved in Cry1Ac resistance in H. armigera.